TINGKAT MOTIVASI MAHASISWA UKM DALAM MENGIKUTI LATIHAN TENIS LAPANGAN DI UNIVERSITAS ISLAM RIAU - Parakes, Oki Fhutuh; Jatra, Rices (YLPK Mahardhika, 2025)
The problem in this study is that students tend not to use their free time for exercise. Existing facilities are sometimes underutilized or not used at all by students for playing tennis. The awareness of the benefits of exercise is not yet evenly understood among students, causing many of them to spend their free time on leisurely activities rather than engaging in sports, particularly tennis. On the other hand, the management of the Student Activity Unit (UKM) still requires strengthening, such as the insufficient number of coaches and the limited availability of supporting activities such as competitions or specialized training, which also affect students’ motivation to participate actively. The purpose of this study is to determine the Level of Motivation of Student Activity Unit (UKM) Members in participating in Tennis Training at the Islamic University of Riau. This research is a descriptive quantitative study. The population consists of UKM students participating in tennis training at the Islamic University of Riau, totalling 22 individuals. The sampling technique used is total sampling, so the sample in this study also consists of 22 students. The research instrument used was a questionnaire with a Likert scale. Based on the results, the level of motivation of UKM students in participating in tennis training at the Islamic University of Riau falls within the range of 61–80%, categorised as strong, with a percentage of 74.89%.